Utilization of Avocado (Persea americana Mill.) Seeds and Cinnamon (Cinnamomum burmannii) as A Functional Powder Drinks - Arum Dwi Agustin (Journal of Science and Technology Research for Pharmacy, 2022)
Functional powder drinks are drinks that if consumed can have a positive influence on the health of the body. Avocado seeds and cinnamon have bioactive compounds where these compounds have antioxidant properties that are good for our bodies. This research aims to find out the physical quality and antioxidant activity of functional powder drinks from avocado seeds and cinnamon. Methods and types of research conducted are quantitative research using descriptive design. Testing parameters include tests of physical quality, qualitative and quantitative flavonoid tests as well as antioxidant activity tests using UV-Vis Spectrophotometers. The results of physical quality tests showed functional beverage powder has a smooth texture, a whitish brown color, a distinctive smell of spices, and a distinctive sweetness of spices with a pH of 6,569. Qualitative tests of flavonoids showed the results of functional powder drinks positive containing flavonoid compounds due to the presence of red color formed, then continued with quantitative tests flavonoids obtained flavonoid levels of 12.201%. Antioxidant test results in functional powder drinks showed IC50 value of 128,422 mg/L which belongs to the category of moderate-level antioxidants.